2021
DOI: 10.3389/fpsyt.2021.789622
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Childhood Left-Behind Experience and Quality of Life Among Chinese University Freshmen: Place of Origin Matters

Abstract: Background: Childhood left-behind experience (LBE) has a long-term detrimental effect on the mental health of Chinese University students, but it remains unclear whether childhood LBE negatively impacts the quality of life (QOL) of University students and whether the LBE–QOL association differs between students of rural origin and students of urban origin. This study examined the LBE–QOL relationship and the interactive effect between LBE and place of origin on QOL among Chinese University freshmen.Methods: By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our study results suggested that university freshmen suffered from sleep disturbance, which was associated with poor QoL. School-based preventions and interventions should be considered and implemented to prevent sleep disturbance and hence the reduced QoL of those potentially affected ( 66 ). For instance, psychological counseling services through face-to-face care and telehealth should be both adopted.…”
Section: Discussionmentioning
confidence: 76%
“…Our study results suggested that university freshmen suffered from sleep disturbance, which was associated with poor QoL. School-based preventions and interventions should be considered and implemented to prevent sleep disturbance and hence the reduced QoL of those potentially affected ( 66 ). For instance, psychological counseling services through face-to-face care and telehealth should be both adopted.…”
Section: Discussionmentioning
confidence: 76%
“…The past four decades in China have witnessed profound social changes. Paramount among these changes is the massive migration of labor, both within cities and from rural areas to urban centers [1][2][3]. For example, in 2021, the total number of internal migrants in China, which included both categories of migration, stood at 384.7 million [4].…”
Section: Introductionmentioning
confidence: 99%
“… 13 However, due to the high population mobility in China’s transforming society, such as long-term business travel by urban workers and rural young labourers moving to cities for work, a large number of older Chinese parents are left behind in their home communities, unable to receive adequate daily care and timely emotional support from their adult children who are living elsewhere. 14 15 Numerous studies have demonstrated that left-behind elderly individuals are at a higher risk of chronic physical illnesses, loneliness, and depressive and anxiety symptoms than non-left-behind elderly individuals. 15–17 Because these factors have been linked to an increased risk of cognitive impairment, 18–21 left-behind older adults may have poorer cognitive function than those with nearby family members.…”
Section: Introductionmentioning
confidence: 99%